Operating Protocol and Networking Issues of a Telemedicine Platform Integrating from Wireless Home Sensors to the Hospital Information System. (13th March 2013) - Donati, Massimiliano; Bacchillone, Tony; Fanucci, Luca; Saponara, Sergio; Costalli, Filippo
Abstract : Chronic heart failure (CHF) is among the major causes of hospitalization for elderly citizens. Its considerable impact on patient quality of life, the resources congestion, and the related costs can be efficiently mitigated using remote wireless biosensors networks placed at patient home, able to communicate in secure way over the public Internet with the cardiology departmental Hospital Information System (HIS). In this way, physicians can monitor the situation of several patients at distance and quickly realize and act alterations in vital parameters. In this scenario, the Health@Home (H@H) platform is conceived. The pool of Bluetooth sensors enables patients to daily collect vital signs at home in noninvasive fashion. A home gateway receives and processes all signals before sending them to a server node in charge of interfacing with the usual HIS. The novel concept of operating protocol (OP) represents a list of actions, remotely configurable, that the domestic network has to follow (required measurements, transmissions, comparisons with personalized thresholds, etc.). The first medical tests on 30 patients (1 month) allowed to verify the model, both from the patient and the medical perspective. The main evaluation metrics were usability, flexibility, and reliability of the communication from sensors to HIS.